Những câu hỏi liên quan
QN
Xem chi tiết
PK
Xem chi tiết
IY
Xem chi tiết
HA
Xem chi tiết
NA
1 tháng 11 2019 lúc 21:50

Vì a+b+c+d=0\(\Rightarrow a+b+c=-d\Rightarrow ac+bc+c^2=-cd\)

\(\Rightarrow\)\(ab-cd=ab+ac+bc+c^2=\left(a+c\right)\left(b+c\right)\)

Tương tự ta có \(bc-ad=\left(a+b\right)\left(a+c\right)\)

                        \(ac-bd=\left(a+b\right)\left(b+c\right)\)

Từ 3 điều trên ta suy ra đpcm

Bình luận (0)
 Khách vãng lai đã xóa
HT
Xem chi tiết
TT
Xem chi tiết
VD
Xem chi tiết
NH
Xem chi tiết
TN
13 tháng 12 2024 lúc 20:24

Ngu

 

Bình luận (0)
H24
Xem chi tiết
H24
Xem chi tiết